MACRO NUTRIENTS UPTAKE OF FORAGE GRASSES AT DIFFERENT SALINITY STRESSES - Kusmiyati, F.; Purbajanti, E.D.; Kristanto, B.A. (Diponegoro University, 2009)
The high concentration of sodium chloride (NaCl) in saline soils has negative effects on the growth ofmost plants. The experiment was designed to evaluate macro nutrient uptake (Nitrogen, Phosphorus andPotassium) of forage grasses at different NaCl concentrations in growth media. The experiment wasconducted in a greenhouse at Forage Crops Laboratory of Animal Agriculture Faculty, Diponegoro University.Split plot design was used to arrange the experiment. The main plot was forage grasses (Elephant grass(Pennisetum purpureum ) and King grass (Pennisetum hybrida)). The sub plot was NaCl concentrationin growth media (0, 150, and 300 mM). The nitrogen (N), phosphorus (P) and potassium (K) uptake in shootand root of plant were measured. The result indicated increasing NaCl concentration in growth mediasignificantly decreased the N, P and K uptake in root and shoot of the elephant grass and king grass. Thepercentage reduction percentage of N, P and K uptake at 150 mM and 300 mM were high in elephant grassand king grass. It can be concluded that based on nitrogen, phosphorus and potassium uptake, elephantgrass and king grass are not tolerant to strong and very strong saline soil.